Flip angle optimization for balanced SSFP: Cardiac cine imaging following the application of standard extracellular contrast agent (gadobutrol). Issue 1 (21st April 2017) - Kuetting, Daniel L.R.; Dabir, Darius; Luetkens, Julian; Feisst, Andreas; Homsi, Rami; Thomas, Daniel; Schild, Hans H.; Sprinkart, Alois M.
Abstract : Purpose: To investigate the effect of the flip angle (FA) on the blood‐myocardium contrast and to define the FA leading to highest image quality in contrast‐enhanced balanced steady‐state free precession (bSSFP) images. bSSFP images provide excellent contrast between myocardium and blood with high signal‐to‐noise and contrast‐to‐noise ratios (SNR, CNR). In clinical practice, bSSFP images are typically acquired following the injection of extracellular contrast agents (ECAs), although ECAs decrease the blood‐myocardium contrast. Materials and Methods: First, a theoretical optimization was performed to determine the FA that maximizes CNR in bSSFP imaging 2–20 minutes after application of ECA. Second signal‐ratios, contrast, SNR, and CNR were assessed in vivo in 25 patients in bSSFP images at 1.5T acquired before (FA = 50°) and 10–15 minutes after (FAs = 50°, 80°, 90°, 100°) application of a double‐dose contrast agent. Image quality was assessed by two readers. Results: Simulations yielded FAs in the range of 85–100° for optimal CNR in contrast‐enhanced images. In vivo comparison of conventionally acquired cine images (FA 50°) showed an increase in CNR between blood and myocardium by 57% in diastole and 78% in systole in adapted contrast‐enhanced bSSFP images (FA 100°). Contrast‐enhanced images with an FA of 100° were rated highest in image quality assessment. Conclusion: By means of FA adaptation a similar blood‐myocardium contrast can be achieved in contrast‐enhanced bSSFP as in unenhanced bSSFP imaging with an increase in CNR. Level of Evidence: 1 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2018;47:255–261.